Ability of the United States Air Force Family Needs Screener to Predict Child Maltreatment: A Prospective Study. (2nd July 2020) - McCarthy, Randy J.; Milner, Joel S.; Walker, Margaret H.; Besetsny, Leasley K.; Oliver, Mark A.
Abstract: In the current study, we examined the extent to which the United States Air Force Family Needs Screener (FNS)—a scale that purportedly measures risk for child maltreatment–predicted future child maltreatment in a group of 87, 982 mothers. Mothers' FNS total scores predicted future child maltreatment overall (i.e., any type of maltreatment) and for individual types of child maltreatment (i.e., child physical abuse, child emotional abuse, and child neglect). Further, results did not vary across Air Force installations. Beyond the standard dichotomous FNS classifications (Low-Needs and Low-Needs), the finding that as individual FNS total scores increased so did the likelihood of future child maltreatment suggests that mothers with the highest FNS scores—even among those deemed high needs—may warrant special attention.